2014
DOI: 10.3171/2013.12.peds13188
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring changes in pediatric spinal deformity surgery: a single-institution experience

Abstract: Object Intraoperative monitoring of the spinal cord has become the standard of care during surgery for pediatric spinal deformity correction. The use of both somatosensory and motor evoked potentials has dramatically increased the sensitivity and specificity of detecting intraoperative neurophysiological changes to the spinal cord, which assists in the intraoperative decision-making process. The authors report on a large, single-center experience with neuromonitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…5 Multimodality neuromonitoring of SSEPs and TceMEPs allows for a greater level of specificity regarding patient outcome after spinal deformity surgery. 2 Nuwer et al observed a sensitivity level of 92% and a specificity level of 98% for SSEP monitoring, in terms of new postoperative motor deficits.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…5 Multimodality neuromonitoring of SSEPs and TceMEPs allows for a greater level of specificity regarding patient outcome after spinal deformity surgery. 2 Nuwer et al observed a sensitivity level of 92% and a specificity level of 98% for SSEP monitoring, in terms of new postoperative motor deficits.…”
mentioning
confidence: 99%
“…1 Last, neurological disorders, such as seizures, were once thought to be a contraindication to TceMEPs. [1][2][3]8 According to MacDonald and colleagues, the incidence of seizures was 0.03% and the incidence of bite injuries was 0.2%. 6 Therefore, a risk/benefit analysis should be performed prior to utilizing TceMEPs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of IOM in spinal deformity surgery reported an end result occurrence (postoperative deficit) of less than 1%. Hence, it was natural that specificity of IOM was around 99% and sensitivity varied according to wake-up test result [2,14]. Meanwhile, in the surgery for intramedullary tumour, at which postoperative neurologic deficit occur at higher rate and wake-up test is rarely applicable, the sensitivity is still high but specificity comes out less accurately.…”
Section: Predictability Of Mep and Ssep For Postoperative Motor Deficitmentioning
confidence: 99%